Impact of radiotherapy protocol adherence in NSCLC patients treated with concurrent chemoradiation: RTQA results of the PET-Plan trial. (October 2021) - Gkika, Eleni; Schimek-Jasch, Tanja; Kremp, Stephanie; Lenz, Stefan; Stockinger, Marcus; Schaefer-Schuler, Andrea; Mix, Michael; Küsters, Andreas; Tosch, Marco; Hehr, Thomas; Eschmann, Susanne Martina; Bultel, Yves-Pierre; et al.
Highlights: Non-adherence to the radiotherapy protocol was associated with a worse OS and loco-regional control.These results were significant also in the subgroup of patients receiving ≥ 60 Gy. These results were significant also in the subgroup of patients receiving ≥ 60 Gy. Patients with major deviations in normal tissue delineation and/or dose constraints had a worse OS. These results underline the importance of RTQA. Abstract: Introduction: The success of intensification and personalisation of the curative treatment of non-small cell lung cancer (NSCLC) is strongly associated with the precision in radiotherapy. Here, we evaluate the impact of radiotherapy protocol adherence in a prospective multicentre trial. Methods: In the open-label, randomised, controlled PET-Plan trial, patients with inoperable NSCLC were randomized at a 1:1 ratio regarding the target volume delineation informed by 1 F-FDG PET and CT plus elective nodal irradiation (arm A) or target volumes informed by PET alone (arm B) and received iso-toxically dose-escalated concurrent chemoradiation. The prospectively organised quality assurance program (RTQA) included individual case review by predefined criteria. For evaluation, protocol adherence was scored as per protocol (pP), with minor (miD), intermediate (inD) and major (maD) deviations. In order to exclude biases through patients who discontinued treatment, patients who received ≥60 Gy were additionally analysed. Results: Between 05/2009–11/2016, 205 patients were randomized, 204 patients started treatment according to protocol of which 31 (15%) patients had maD. Patients with maD had an inferior overall survival (OS) (HR 2.9, 95% CI 1.8–4.4, p  < 0.0001) and a higher risk of loco-regional progression (HR 5.7, 95% CI 2.7–11.1, p  < 0.0001). These results were significant also in the subgroup of patients receiving ≥ 60 Gy. Patients with maD concerning normal tissue delineation and/or dose constraints had a worse OS ( p  = 0.006) although no higher incidence of grade ≥ 3 toxicities. Conclusions: Non-adherence to the radiotherapy protocol was associated with an inferior OS and loco-regional control. These results underline the importance of RTQA.